Scientific families in Wasit and their impact on public life (132 AH / 656 AH) (749/1258 AD) - فيصل برغش المياحي . جليلة (Journal of College of Education, 2019)
At the conclusion of our research scientific families in Wasit and its impact on public life (132 e-656 e / 749-1258 m) must be recorded the most important findings, which we reached, as the study showed us many of the results, and prove a lot of facts, including: First, the city of Wasit received a great deal of care from the historians and the Baldans. They did not know much about this Islamic city, which dates back to the first century AH. Historians differed about the date of its construction. The historian Al-Wasseti said that its construction took place between the years (75_78 / 694_697) Historians of different dates. Secondly, a large number of scientific families have emerged in Wasit and their scholars contributed to the flourishing of educational institutions from the establishment of mosques, schools and interconnections. Mosques are the first places of education. In addition to being a place of worship for Muslims, the mosque became a base for education. Which contributed greatly to the development of the intellectual movement, and linking is considered the most important Sufi centers where the practice of Sufism and asceticism of the world in addition to performing religious and social functions. Third: _ The scholars of families in the city of Wasit in the religious sciences, including the science of readings, which were accredited in reading the Koran and modern science and jurisprudence scientific scholars participated actively in the conservation of the novel of the Hadith, has included a large group of scientists Wasit who participated In this science, the most prominent of them is the son of al-Baghdadi al-Wasiti (d. 312 AH). They did not neglect the study of mental sciences such as arithmetic, statutes, astronomy and astrology. Fourth: _ The scientists of scientific families have a very important impact on the various religious functions of Iftaa and speech as well as the judiciary and some of the scientific families in Wasit took over the position of the judiciary, which is one of the most sensitive positions in the state, and foremost Judge Ahmed bin Mohammed bin Mansour Abu Jaafar Damagani Al-Wasti (355 AH / 966 AD) as well as the Mandae family ", a house known for justice, justice and science, including Judge Ahmad bin Bakhtiar bin Ali bin Mohammed al-Mandai born in 476 AH / 1083 AD (552 AH / 1157 AD) Fifth, and the scholars of Wasit significant impact in the civil service, this is a proof of their enjoyment of wide powers, including the post of Hesba has known this institution since the Umayyad era, despite the scarcity of information about the mandate and the post of writer construction. The role of family scientists in the political, social and economic life and the official positions they assumed in the ministry as well as some of them in the military field took great military tasks such as Al-Sharaibi, which was the successor of the Caliph al-Mustansir al-Abbasi and his son and was the commander of the military at that time, and did not overlook the great responsibilities assumed by most family scientists , But they were not far from the community, as they sought to serve the people, so they managed to gain their own, and that these scientists are the ones who carry the religious sciences, which received the most public attention.